2022
DOI: 10.1134/s1070328422110082
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Complexes of 4-Aminoantipyrine Derivatives and Their Antimicrobial Applications

Abstract: Transition metal complexes of 4-aminoantipyrine derivatives have been gaining great interest due to their rich coordination chemistry and potential applications in the field of pharmaceutical science. The presence of a free amine and a cyclic ketone functionality makes 4-aminoantipyrine an attractive amphoteric substrate for Schiff base formation. Varieties of aldehydes/ketones or amines of versatile steric, electronic and functional nature could be condensed with the 4-aminoantipyrine motif to obtain the liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…vulgaris ) and fungi ( C . albicans ), which were found to be good activity about 65 μM 47 . Al‐Obaidi reported that dinuclear Cu (II) and Co (II) complexes of Schiff base derived from 4‐aminoantipyrine with salicylaldehyde were prepared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…vulgaris ) and fungi ( C . albicans ), which were found to be good activity about 65 μM 47 . Al‐Obaidi reported that dinuclear Cu (II) and Co (II) complexes of Schiff base derived from 4‐aminoantipyrine with salicylaldehyde were prepared.…”
Section: Resultsmentioning
confidence: 99%
“…Four metal complexes showed moderate antimicrobial activity against bacteria (S. aureus, B. subtilis, and P. vulgaris) and fungi (C. albicans), which were found to be good activity about 65 μM. 47 Al-Obaidi reported that dinuclear Cu (II) and Co (II) complexes of Schiff base derived from 4-aminoantipyrine with salicylaldehyde were prepared. Copper (II) complexes have moderate effect on S. aureus.…”
Section: Antibacterial Evaluationmentioning
confidence: 99%
“…Antipyrine and its derivatives have provoked boundless interest, especially in medicine, due to the wide range of pharmacological activities and therapeutic applications, such as the antibacterial, antifungal, analgesic, antitumor, antipyretic, and anti-inflammatory activity of antipyrine. [23][24][25][26] A few intriguing fluorescent sensors based on antipyrine have also been produced. [27][28][29][30] Most of the effort has been concentrated on synthesis, structure characterization, and biological evaluation of antipyrine derivatives.…”
Section: Introductionmentioning
confidence: 99%